Enhancing Poetry Writing Skills Using Keyword Techniques for Eleventh-Grade Students at SMK Penerbangan Cakra Nusantara Denpasar - ., Khazin; Dzunnurain, Muhammad (Journal of Language, Literature and Teaching, 2024)
This research aims to improve poetry writing skills using the keyword technique. The research method employed is Classroom Action Research (CAR), which cycles through planning, implementation, observation, and reflection. The subjects of the study are the eleventh-grade students of SMK Penerbangan Cakra Nusantara Denpasar. The research data includes tests, observations, and documentation. The instruments used are student observation sheets and skill assessment sheets. Observation data will be analyzed descriptively, while test results will be analyzed using averages. The study concludes: 1) The steps for implementing the keyword technique can improve the poetry writing learning process and outcomes for students, and 2) Selecting poetry writing themes based on local values facilitates students in expressing their ideas.